Feed-forward control of piezo-electric based in a micro-forging machine - Indra Wiguna Chandra (2014)
In recent years, growing industries in the field of miniaturization are notable. With improvements in technology, there will also be an increase in demand to produce smaller micro systems. In order to produce high quality micro system, equipment that able to provide precise movement is needed. Piezo-electric actuator is then selected due to its ability to provide high accuracy movement and its fast response. However, nonlinearity factors of piezo-electric actuator, which mainly happens in the form of hysteresis, might cause error in the performance of the actuator. Therefore, the main purpose of this project is to characterize and develop mathematical model for piezo-electric actuator system and design a controller to control the output of the system and maintain it at constant strain rate. In first part of the project, linear approximation mathematical model of the system was determined. Then the model will be used to design PI and PID controller for the system. MATLAB’s sisotool, tuning method and result comparison were used to determine the best PI and PID controller’s parameters. In the latter part of the project, the use of feed-forward controller, which based on Prandtl Ishlinskii inverse model, was introduced to minimize the effect of non-linearity in the system. A comparison of result was done to check the ability of the feed-forward to reduce non-linearity effect in piezo-electric system. Based on this project, some conclusions can be drawn. The first conclusion is the capability of linear approximation mathematical model to represent the actual system. The second conclusion is the capability of feed-forward controller to improve the result by reducing non-linearity. In the end of the project, a constant strain rate value, which was the main requirement for the control system, was achieved.